Insecticidal Mechanism of Botanical Crude Extracts and Their Silver Nanoliquids on Phenacoccus solenopsis - Mariappan Madasamy; Kitherian Sahayaraj; Samy M. Sayed; Laila A. Al-Shuraym; Parthas Selvaraj; Sayed-Ashraf El-Arnaouty; Koilraj Madasamy (Toxics, 2023)
In recent years, intensive studies have been carried out on the management of agricultural insect pests using botanical insecticides in order to decrease the associated environmental hazards. Many studies have tested and characterized the toxic action of plant extracts. Four plant extracts (Justicia adhatoda, Ipomea carnea, Pongamia glabra, and Annona squamosa) containing silver nanoparticles (AgNPs) were studied for their effects on Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) using the leaf dip method. The effects were estimated based on assays of hydrolytic enzyme (amylase, protease, lipase, acid phosphatase, glycosidase, trehalase, phospholipase A2, and invertase) and detoxification enzyme (esterase and lactate dehydrogenase) levels; macromolecular content (total body protein, carbohydrate, and lipid); and protein profile. The results show that the total body of P. solenopsis contains trypsin, pepsin, invertase, lipase, and amylase, whereas J. adathoda and I. carnea aqueous extracts considerably decreased the protease and phospholipase A2 levels, and A. squamosa aqueous extract dramatically increased the trehalase level in a dose-dependent manner. The enzyme levels were dramatically decreased by P. glabura-AgNPs (invertase, protease, trehalase, lipase, and phospholipase A2); I. carnea-AgNPs (invertase, lipase, and phospholipase A2); A. squamosa-AgNPs (protease, phospholipase A2); and J. adathoda-AgNPs (protease, lipase, and acid phosphatase). Plant extracts and their AgNPs significantly reduced P. solenopsis esterase and lactate dehydrogenase levels in a dose-dependent manner. At higher concentrations (10%), all of the investigated plants and their AgNPs consistently decreased the total body carbohydrate, protein, and fat levels. It is clear that the plant extracts, either crude or together with AgNPs, may result in the insects having inadequate nutritional capacity, which will impact on all critical actions of the affected hydrolytic and detoxication enzymes.